Homework or home sweet home: patient and provider perspectives on remote monitoring lung function at home - Rachel Johnson-Koenke; Marcie Lee; Amber Lane; Summer Huang; Matthew Griffith (BMC Pulmonary Medicine, 2026)
Abstract Background Amyotrophic Lateral Sclerosis (ALS) affects approximately 30,000 people in the United States at any given time, 80% of whom will die from a respiratory complication of this disease. Regularly monitoring lung function is crucial for these people to guide appropriate treatment and establish prognosis. Shifting disease monitoring and diagnostic testing from clinic to home could provide advantages to patients with ALS and other advanced stage chronic conditions who have complex care needs. Objective To explore Veteran and provider perspectives of a home spirometry program. Design and participants We conducted semi-structured interviews with providers in ALS clinics and Veterans living with ALS who participated in a home spirometry program at two VA medical centers. Approach Our team used the Practical, Robust Implementation and Sustainability Model (PRISM) to guide our conventional content analysis and thematic analysis. Key results We generated four main patterns and themes: benefits and challenges, suggestions for the future, empowering patients to take charge of their health and trusting the results of home spirometry and care providers. Conclusions These findings suggest that patients can benefit from using a home telemedicine testing device.